A104: Aggressive Erosive Synovitis in Juvenile Idiopathic Arthritis. Issue 11 (March 2014) - Chédeville, Gaëlle; Azouz, Michel; Scuccimarri, Rosie
Abstract : Background/Purpose: Plain radiographs (x‐rays) are useful in the evaluation of children with JIA. Bone erosions are one of the finding that can be seen on x‐rays. However, they are most often reported in the polyarticular RF+ subtype of JIA and are rare in most other subtypes. Methods: Herein 3 patients with JIA are presented whose diagnoses were questioned after plain x‐rays were obtained. MRI later revealed significant erosive disease in these patients. Results: Case 1 : A 14 yo male presented with a monoarthritis of the left wrist. Initial x‐rays were normal. His work‐up was unremarkable. His inflammatory markers were normal. He was thus diagnosed with JIA–oligoarthritis. After 6 months in remission, after the use of an NSAID, he flared in the same joint. Repeat x‐rays showed a radiolucent area with associated sclerosis in the scaphoid of unclear etiology. An MRI was thus requested. It revealed synovitis associated with erosive disease. Post gadolinium injection, a geode in the scaphoid bone with marked synovial enhancement visible within this erosion was detected. He underwent a joint injection which put him into remission. Repeat x‐rays one year later, revealed unchanged findings likely corresponding to the non‐healed erosion. Case 2 : An 11 yo HLA B27 + male diagnosed with ERA with polyarthritis of the lower limbs and sacroiliac joints was treated with methotrexate and an NSAID. Investigations ruled out IBD and the arthritis was felt to be well controlled despite persistently elevated inflammatory markers of unclear etiology. He presented with a severe flare in his knees and ankles. X‐rays revealed well‐defined lytic lesions in the anterior aspect of the proximal tibial metaphysis just below the growth plate bilaterally. Given the concern of an infiltrative process, an MRI was obtained. Post gadolinium injection, a large erosion of the tibial plateau with marked synovial enhancement within this erosion was seen, as well as a knee synovitis. Etanercept was started. Case 3 : An 8 yo male presented with a monoarthritis of the right wrist evolving for five months after an initial minor trauma. X‐rays revealed advanced bone maturation of the right wrist as well as a sclerotic lesion of the hamate. Given the initial trauma, an MRI was obtained which demonstrated very extensive bone marrow edema, synovitis, tenosynovitis and a large erosion within the hamate. A diagnosis of JIA–oligoarthritis was made. He underwent a joint injection with good disease control. Conclusion: Large erosions are not typical for some JIA subtypes such as oligoarthritis and ERA. Findings on x‐rays led the treating physicians to question the underlying diagnosis however, MRI revealed very aggressive synovitis of the wrist and knee in these patients. MRI was useful to demonstrate the presence of synovial enhancement within the eroded bone and helped rule out another diagnosis. Awareness of this type of aggressive arthritis is needed so that patients are not over‐investigated and prompt treatment can be offered.